The Power of Progressive Islamic Identity in Managing Charitable Activities in the Field of Education at Muhammadiyah University Malang - Basri, La; Tobroni, Tobroni; Damanik, Fritz Hotman Syahmahita (Universitas Muhammadiyah Sorong, 2025)
This study discusses the role of Progressive Islam identity in the management of educational charitable activities at Muhammadiyah University Malang (UMM). Since its establishment, Muhammadiyah has emphasized the idea of progressive Islam, which is reflected in various charitable activities, including education. UMM, as a leading Muhammadiyah university, plays an important role in implementing Progressive Islam values in the field of education. This study aims to explore how this identity is applied in the management of education at UMM and the relationship between ideology and managerial practices. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation related to education management policies and practices. The results show that Progressive Islam identity is the foundation for curriculum development, educational policy, and academic culture at UMM, despite challenges in consistent implementation. This identity strengthens the university's moral legitimacy, curriculum innovation, management integrity, and social reputation, making it a transformational force in educational management.